USE OF COGNITIVE STRATEGIES IN PROMOTING STUDENTS' ENGLISH READING COMPREHENSION SKILLS - Muhammad Tahir; Ladipin (CV Naskah Aceh, 2023)
In mastering reading skills, many students face several problems in reading such as a lack of vocabulary which makes it difficult for them to understand the text and they do not understand the strategies. In fact, the purpose of reading is to comprehend and understand what is being read. Therefore, it is the teacher's responsibility to apply appropriate methods or strategies to achieve reading goals for students. The research problem in this study is how does the use of cognitive strategies encourage students' reading abilities? The aim of this research is to determine the process of using cognitive strategies to encourage students' reading comprehension skills. Data collection uses tests and treatment (training).